2012
DOI: 10.3855/jidc.2268
|View full text |Cite
|
Sign up to set email alerts
|

blaIMP and blaVIM mediated carbapenem resistance in Pseudomonas and Acinetobacter species in India

Abstract: Introduction: The emergence and rapid spread of bla IMP and bla VIM metallo-beta-lactamase (MBL) producing Gram-negative bacteria causing nosocomial infections are of concern worldwide due to limited treatment options. Methodology: A total of 179 nonreplicate, consecutive, carbapenem resistant Pseudomonas aeruginosa (61), Acinetobacter baumannii (116), Acinetobacter lwoffii (1) and Pseudomonas stutzeri (1) isolated from patients hospitalized for 48 hours or more were included in the study. The minimum inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 17 publications
11
45
1
Order By: Relevance
“…Considering sample wise distribution, most samples from which non-fermenters were isolated were those from tracheal aspirate (34.12%) followed by blood (25.67%), pus (17.22%), and urine (8.44%). Amudhan et al, had predominant NFGNB isolates from respiratory secretions (Amudhan et al, 2012). Kalidas et al, isolated non-fermenters predominantly from pus (Rit et al, 2013).…”
Section: Risk Factor Assessment (Table 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering sample wise distribution, most samples from which non-fermenters were isolated were those from tracheal aspirate (34.12%) followed by blood (25.67%), pus (17.22%), and urine (8.44%). Amudhan et al, had predominant NFGNB isolates from respiratory secretions (Amudhan et al, 2012). Kalidas et al, isolated non-fermenters predominantly from pus (Rit et al, 2013).…”
Section: Risk Factor Assessment (Table 1)mentioning
confidence: 99%
“…Total 27.65% of isolates were positive for VIM. Amudhan et al, (2012) reported 45.68% of resistant isolates to harbour VIM. 11.7%isolates were positive for OXA-23, OXA-51, NDM and VIM.…”
Section: Risk Factor Assessment (Table 1)mentioning
confidence: 99%
“…The presence of the genes encoding KPC, MBLs of IMP, VIM, SIM and NDM class [4,[5][6][7][8] and OXA β-lactamases (bla OXA-51-like , bla OXA-23-like , bla OXA-40-like , bla OXA-58-like and bla OXA-143-5 like ) genes [18] was determined by PCR as previously described. The amplicons of the selected representative isolates were column-purified (QIAquick PCR purification kit, Inel Medicinska tehnika, Zagreb) and subjected to sequencing by the Macrogen sequencing service (South Korea) with the same primers used for PCR in order to determine the identity of the enzyme.…”
Section: 3molecular Characterization Of β-Lactamasesmentioning
confidence: 99%
“…Rarely, resistance can occurr because of porin loss (CarO) or overexpression of efflux pumps [3]. Acquired carbapenem resistance in A. baumannii can also be mediated by acquired carbapenemases of class A (KPC) [4], metallo-β-lactamases (MBLs) of IMP, VIM, SIM and NDM family [5][6][7][8] and carbapenem-hydrolyzing oxacillinases (CHDL) (OXA-23-like, OXA-40-like, OXA-58-like, OXA-143-like and OXA-235-like [9][10][11][12]. From 2008 carbapenem-resistant A. baumannii emerged with increasing frequency in most hospital centers in Croatia and became an important public health problem as shown by the multicenter study conducted in Northern Croatia and Istria demonstrating that OXA-40-like and OXA-58-like were the dominant types of acquired CHDL in Croatia.…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenems are still the drugs of choice to treat infections associated with the drugresistant NFGN bacteria [2,6]. Nevertheless, carbapenem resistance among Pseudomonas and Acinetobacter has emerged and become widespread, demanding increased efforts to treat infection with chemotherapy, using polymyxin B and tigecycline, the last therapeutic option [5,7,8].…”
Section: Introductionmentioning
confidence: 99%